An h-adaptive implicit immersed boundary-lattice Boltzmann flux solver based on JASMIN AMR package. (15th January 2018) - Zhang, Pan; Xia, Zhenhua; Cai, Qingdong
Highlights: The IB-LBFS method is successfully integrated with adaptive mesh refinement technique. AMR-IB-LBFS is used to simulate four benchmark problems accurately and efficiently. An alternative AMR-compatible momentum-based splitting is proposed for IB-LBFS. Abstract: In order to efficiently simulate flows with complex geometries, an implicit immersed boundary-lattice Boltzmann flux solver (IB-LBFS) combined with an h-adaptive mesh refinement (AMR) technology is proposed and implemented on JASMIN infrastructure. In the present implementation, the original velocity-splitting IB-LBFS is modified by a momentum-splitting during the factional step. Four benchmark problems are used to validate the present method, including the flow over a stationary circular cylinder, the sedimentation of a two-dimensional elliptical particle, the flow around a stationary sphere and the sedimentation of a single sphere. The simulated results are in good agreements with previously published data, which demonstrates the accuracy and the capability of the proposed method in simulating flow problems with stationary or moving boundaries.